2009
DOI: 10.1007/s00702-009-0273-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutational screening of the mortalin gene (HSPA9) in Parkinson’s disease

Abstract: Mortalin is a mitochondrial chaperone of the heat shock protein 70 family. Mortalin plays a central role in mitochondrial biogenesis through its capacity to direct the import of nuclear-encoded proteins into the mitochondria. As mitochondrial dysfunction has been involved in Parkinson's disease (PD), changes in mortalin function and expression could manifest as a higher risk of developing PD. In agreement with this, mortalin expression was decreased in the mitochondrial fraction of neurons from the substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…Consistent with this role, several studies have shown that mortalin may be implicated in the progression of neurodegenerative and protein aggregation disorders, such as Parkinson and Alzheimer (Burbulla et al 2010;De Mena et al 2009;Deocaris et al 2008;Deocaris et al 2007;Koren et al 2009;Shi et al 2008). Moreover, when mammalian mitochondria are challenged with an imported protein with a strong tendency to form aggregates, the mitochondrial unfolded protein response (mUPR) is activated (Aldridge et al 2007;Zhao et al 2002).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 94%
“…Consistent with this role, several studies have shown that mortalin may be implicated in the progression of neurodegenerative and protein aggregation disorders, such as Parkinson and Alzheimer (Burbulla et al 2010;De Mena et al 2009;Deocaris et al 2008;Deocaris et al 2007;Koren et al 2009;Shi et al 2008). Moreover, when mammalian mitochondria are challenged with an imported protein with a strong tendency to form aggregates, the mitochondrial unfolded protein response (mUPR) is activated (Aldridge et al 2007;Zhao et al 2002).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 94%
“…Using an unbiased quantitative proteomic approach, Jin and colleagues have reported that mtHsp70 levels are decreased in the mitochondrial fraction of the substantia nigra in Parkinson's patients (Jin et al 2006). Furthermore, several variants of the gene that codes for mtHsp70 (HSPA9) have been found in a small cohort of late-onset Parkinson's patients (De Mena et al 2009). Some of the phenotypes associated with mtHsp70 mutations are characterized by mitochondrial dysfunction, such as Njemini et al 2007 respiratory incompetency and increased susceptibility to oxidative stress (Burbulla et al 2010;Goswami et al 2012).…”
Section: Heat Shock Proteins In Neurodegenerative Disorders and Agingmentioning
confidence: 99%
“…On the other hand, deficiency in mortalin has been well connected to the age-related pathologies including Alzheimer and Parkinson diseases (28,(31)(32)(33). Genomic studies have identified mutants of mortalin in PD patients from Swedish and German populations (31,32). In light of this information and to resolve the functional significance of these mutants in aging and age pathologies, we generated human cells expressing mot-1 or mortalin-PD (mot-PD) mutant proteins.…”
Section: Waf1mentioning
confidence: 99%